Implementation of Ziyadah and Murojaah to Improve Students' Memorization Completeness at MTSN 1 Purworejo - Adilla Intan Nuraini; Aniqoh Aniqoh (Darul Yasin Al Sys, 2026)
The tahfiz programme in Islamic education plays a strategic role in strengthening students’ religious character, yet its effectiveness depends on the balance between adding new memorization and maintaining previously memorized verses. This study examines the implementation of ziyadah and murojaah in the Al-Qur’an tahfiz programme at MTs Negeri 1 Purworejo and analyzes the supporting and inhibiting factors affecting students’ memorization quality and quantity. A qualitative descriptive field design was employed. Data were collected through observation, in-depth interviews, and documentation involving the principal, tahfiz teachers, and students. Data were analyzed using the Miles and Huberman model, with source triangulation applied to ensure validity. The findings show that ziyadah is implemented systematically every morning before regular classes through supporting techniques such as talaqqi and tikrar. Meanwhile, murojaah is conducted both independently and structurally through tasmi’ evaluations and scheduled recitations. These practices positively influence students’ memorization outcomes, as reflected in increased memorization quantity, with many students reaching the targeted juz, and improved memorization quality, indicated by greater fluency, stronger mutqin, and better conformity with tajwid and makhraj. The supporting factors include strong student motivation, full institutional support from the madrasah, competent teachers, and active parental involvement. The inhibiting factors include limited time due to academic workloads, physical fatigue, and students’ lack of concentration. To address these challenges, the madrasah applies motivational learning variations, routine memorization assessments, and consistent murojaah habituation. This study contributes to Islamic education practice by demonstrating that the structured integration of ziyadah and murojaah can sustain tahfiz targets while strengthening both the quantity and quality of students’ Qur’anic memorization.